What Lead to Divorce? Perspectives from a Malaysian Chinese Wife of an Adulterous Husband - Yih, Y.H.; Lau, P.L.; Baranovich, D.; Guan, T.E. (American Scientific Publishers, 2017)
Divorce in marriage is on the rise globally. In Malaysia, the divorce rate is increasing, too. Little research has been done as the issue remains sensitive in Malaysia. In order to understand the phenomenon better, a qualitative research was conducted. Using phenomenological design, the life of a Malaysian Chinese female divorcee is explored. The researchers is interested in: factor that led to divorce. The result showed that extra marital affair is the most significant factor that leads to divorce. However, family influence (children protection) is the factor that keeps the marriage intact. It shows that women have to endure hardship to protect their child, and extra marital affair is the final straw for women in deciding to end their marriage. It is hoped that this research will give a better picture on the increasing divorce rate in Malaysia and would inspire more research to be conducted on this sensitive issue.